Effect of lubricant propertieson the friction coefficient under different temperatures, speeds and loads using a ball-on-disc test. - Figueiredo, Tiago Petermann (2016)
The present study has the objective of evaluating the effect of lubricant features on the friction coefficient by using three different lubricants (two synthetics and one mineral), which are used in automotive transmissions. In order to perform experiments, it was used a ball-on-disc system. The disc was manufactured with the same mechanical properties as transmission gears and the ball was made of 52100 SAE steel. The test parameters were defined based on a dynamic analysis conducted using \"ISOCAD\" which takes into account the geometry of the gear and vehicle dynamics (applied force and speed) during the tribological experiments. In order to set the temperature parameter, the lubricant testing temperature of a standard fuel economy was used. Experiments were conducted in two different lubrication conditions: i (starved) and ii (fully flooded). After the parameters were defined, it was possible to calculate the oil film thickness and, thus define the lubrication regime reached in each condition. Mixed and/or boundary lubrication was obtained in all the tests. Results showed the relationship between the speed and the specific oil film using a Khonsari and Masjedi formulation (2014), which takes into account the effect of surface roughness and, it is based on Downson and Higginson\'s (1981) formulation. The chemical analysis of the lubricant showed a relationship between friction coefficient and the additives used in lubricants. These results also showed the oil performance under different temperatures, speeds and loads. The best results were obtained for a synthetic lubricant.